Contemporary Topics of Pneumonia - Chroneos, Zissis C. (IntechOpen, 2017)
Pneumonia is an inflammatory disease of the air sacs and surrounding interstitium caused by infectious agents or by endogenous inflammatory tissue disorder termed interstitial pneumonia. The present book covers contemporary topics of community, hospital, and health care-related bacterial and viral pneumonia in the setting of drug resistance, environmental exposures, climate change, hormonal influences, and gender. The topic of interstitial pneumonia is brought under the lens of an immune-related connective tissue disease.